Progress towards the implementation of the PRME: Lessons from a South African business school - Baloyi, N.D.; de Jongh, D. (South African Journal of Higher Education, 2020)
One of the growing pillars in support of critical insights to management education is the United Nations’ Principles for Responsible Management Education (PRME). This paper follows on a study conducted on a South African business school’s experience with the PRME as a mechanism to transform business education. Apart from tracking progress regarding PRME, the study also aimed to identify the South African grasp of a transforming management education. In-depth interviews were conducted on the school’s members of faculty who are responsible for tuition and curriculum development. Following analysis of the data, the study found that indeed the PRME initiative is globally relevant and recognised, and has paved the way for hundreds of business schools to start thinking about their curricula. From the single-case inquiry, the study concludes that the case school has made significant progress concerning implementation of the PRME into its curriculum. However, the study also found that the areas of research, communication and peer learning linked to the PRME were commonly shared as areas where improvement is needed.